APPLICATION OF THE LEARNING CYCLE LEARNING MODEL TO THE BIOLOGY LEARNING OUTCOMES OF CLASS - Astuti, Wiwik Wiji; Veryani, Andi Nur (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This type of research is experimental research with a research design in the form of a pretest-posttest control group design. The objectives of carrying out this research are (1) to find out the description of the biology learning outcomes of students who are taught using the Learning Cycle model, (2) to find out the description of the biology learning outcomes of students who are taught without the Learning Cycle model, (3) to find out the differences in the biology learning outcomes of students who are taught with the Learning Cycle model. Learning Cycle with students taught without the Learning Cycle model. The independent variable in this research is the Learning Cycle learning model and the dependent variable is student biology learning outcomes. The subjects in this research were 38 students in class X IPA1 and X IPA2 at SMA Negeri 1 Gowa. The data collection technique in this research is by using students' biology learning outcomes tests. Meanwhile, the data analysis technique is by using descriptive and inferential statistical analysis techniques. The results of this research show that there are differences between students taught using the Learning Cycle model and students taught without the Learning Cycle model. Keywords: Learning Cycle, Learning Outcomes